3120 – DECIPHERING HEMATOPOIETIC STEM CELLS METABOLISM DURING EXPANSION - Lauvinerie, Claire; Villacreces, Arnaud; Desplat, Vanessa; Dumas, Pierre-Yves; Vigon, Isabelle; Pasquet, Jean-Max; Guitart, Amélie (Experimental hematology, 2022)
Mature blood cells have a limited lifespan, therefore, they must be continually renewed. At the apex of this hierarchical process are haematopoietic stem cells (HSC). It is well established that adult bone marrow (ABM) HSC are mainly quiescent with low dividing rates to maintain the stem cell pool. Conversely, during embryogenesis, HSC in the fetal liver (FL) niche proliferate extensively, calling for distinct bioenergetic requirements than ABM-HSC. The link between metabolism and functional capacities of HSC have, however, mostly been studied in adult mouse models. As knowledge on proliferating HSC remains elusive, we propose to investigate on which metabolic pathways expanding FL-HSCs rely on to fulfil their needs. Using omics approaches, we conducted a comparative analysis of quiescent and proliferative HSC metabolism. Bioinformatics evaluation revealed that FL-HSC rely on an oxidative metabolism. Mitochondrial membrane potential of both proliferating and quiescent HSC was assessed as a surrogate for mitochondrial activity, confirming the oxidative metabolic profile of FL-HSC. Functional assays are now being carried out to determine which are the specific metabolic pathways driving FL-HSC expansion both in vitro and in vivo. We are interfering with major metabolic pathways using chemical inhibitors or activators. Validations are performed by flow cytometry and classical read-outs of HSC self-renewal and integrity (colony forming assay and congenic transplant, respectively). This work should shed light on how HSC expand in vivo, which represents a major challenge to improve HSC transplantation therapy in the clinic.